Interindividual variation in ovarian reserve after gonadotoxic treatment in female childhood cancer survivors - a genome-wide association study: results from PanCareLIFE - van der Perk, M E Madeleine; Broer, Linda; Yasui, Yutaka; Laven, Joop S E; Robison, Leslie L; Tissing, Wim J E; Versluys, Birgitta; Bresters, Dorine; Kaspers, Gertjan J L; Lambalk, Cornelis B; Overbeek, Annelies; Loonen, Jacqueline J; et al. (Fertility and sterility, 2024)
OBJECTIVE: To discover new variants associated with low ovarian reserve after gonadotoxic treatment among adult female childhood cancer survivors using a genome-wide association study approach. DESIGN: Genome-wide association study. SETTING: Not applicable. PATIENTS: A discovery cohort of adult female childhood cancer survivors from the pan-European PanCareLIFE cohort (n = 743; median age: 25.8 years), excluding those who received bilateral ovarian irradiation, bilateral oophorectomy, central nervous system or total body irradiation, or stem cell transplantation. Replication was attempted in the US-based St. Jude Lifetime Cohort (n = 391; median age: 31.3 years). EXPOSURE: Female childhood cancer survivors are at risk of therapy-related gonadal impairment. Alkylating agents are well-established risk factors, and the interindividual variability in gonadotoxicity may be explained by genetic polymorphisms. Data were collected in real-life conditions, and cyclophosphamide equivalent doses were used to quantify alkylation agent exposure. MAIN OUTCOME MEASURE: Anti-Müllerian hormone (AMH) levels served as a proxy for ovarian function, and the findings were combined in a meta-analysis. RESULTS: Three genome-wide significant (<5.0 × 10-8) and 16 genome-wide suggestive (<5.0 × 10-6) loci were associated with log-transformed AMH levels, adjusted for cyclophosphamide equivalent dose of alkylating agents, age at diagnosis, and age at study in the PanCareLIFE cohort. On the basis of the effect allele frequency (EAF) (>0.01 if not genome-wide significant), and biologic relevance, 15 single nucleotide polymorphisms were selected for replication. None of the single nucleotide polymorphisms were statistically significantly associated with AMH levels. A meta-analysis indicated that rs78861946 was associated with borderline genome-wide statistical significance (reference/effect allele: C/T; effect allele frequency: 0.04, beta (SE): -0.484 (0.091). CONCLUSION: This study found no genetic variants associated with a lower ovarian reserve after gonadotoxic treatment because the findings of this genome-wide association study were not statistically significant replicated in the replication cohort. Suggestive evidence for the potential importance of 1 variant is briefly discussed, but the lack of statistical significance calls for larger cohort sizes. Because the population of childhood cancer survivors is increasing, large-scale and systematic research is needed to identify genetic variants that could aid predictive risk models of gonadotoxicity as well as fertility preservation options for childhood cancer survivors.
Keywords: Young Adult; Ovarian reserve; childhood cancer; antimülleriánský hormon; Neoplasms; Anti-Mullerian Hormone; Risk Factors; gonadotoxicity; mladý dospělý; Ovarian Reserve; Adolescent; ovariální rezerva; Child; Europe; Cancer Survivors; survivorship; dítě; Adult; Genome-Wide Association Study; dospělí; jednonukleotidový polymorfismus; mladiství; Evropa; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; Humans; rizikové faktory; GWAS; nádory; Antineoplastic Agents, Alkylating; přežívající onkologičtí pacienti; alkylační protinádorové látky; Female; celogenomová asociační studie